KONTRIBUSI PARTISIPASI AKTIF SISWA DAN FASILITAS PRATIKUM TERHADAP HASIL BELAJAR PADA MATA PELAJARAN TEKNIK KERJA BENGKEL (TKB) KELAS X JURUSAN TEKNIK AUDIO VIDEO DI SMK NEGERI 1 BATIPUH - Syafmawandi Irwan; Thamrin Thamrin; Khairi Budayawan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2016)
The objective of the research is the score of student's result test under standart value on subject Teknik Kerja Bengkel (TKB) at SMKN 1 Batipuh. it is caused by several factors less of  active participation of students’ and practise facilities.The purpose of this study was to reveal how big the contribution of active participation of students and  practise facilities and severally on learning outcomes. Data onstudents’ learning outcomesobtainedfrombasic electronicsengineeringteachers.While the active participation of  students’ and practise facilitieswas collected through questionnaires distributed to students by using a Likert scale that has been tested for validity and reliability. The result showed that that (1) active participation of students and practise facilities together contribute significantly to the learning outcomes in SMK Negeri 1 Batipuh by 40.4%, (2) active participation of students’ to contribute significantly to the learning outcomes in SMK Negeri 1 Batipuh of 25.8%, (3) practise facilities contribute significantly to the learning outcomes in SMK Negeri 1 Batipuh of 28.4%. So it can be concluded that active participation students and practise facilities are jointly and individually contribute to the learning outcomes in SMK Negeri 1 Batipuh, increasing active participation studentsand sufficient practise facilities, the higher results learn.